A pediatric case of Bickerstaff's brainstem encephalitis - Ju Yi Park; Kyong Og Ko; Jae Woo Lim; Eun Jung Cheon; Jung Min Yoon; Hyo Jeong Kim (Korean Pediatric Society, 2014)
Bickerstaff's brainstem encephalitis is characterized by ophthalmoplegia, ataxia, and disturbance of consciousness. It is similar to Miller Fisher syndrome, a variant of Guillain-Barre syndrome, in that they share features such as ophthalmoplegia and ataxia. The difference is that patients with Bickerstaff's brainstem encephalitis have impaired consciousness, whereas patients with Miller Fisher syndrome have alert consciousness and areflexia. Here, we report the case of a 3-year-old child who was diagnosed with Bickerstaff's brainstem encephalitis presenting typical clinical features and interesting radiological findings. The patient showed ophthalmoplegia, ataxia, and subsequent stuporous mentality. Brain magnetic resonance imaging revealed high signal intensity in the pons and cerebellum around the 4th ventricle on a T2-weighted image. He was successfully treated with intravenous immunoglobulin. Differentiation of Bickerstaff's brainstem encephalitis and Miller Fisher syndrome is often difficult because they possess many overlapping features. Brain magnetic resonance imaging may be helpful in diagnosing Bickerstaff's brainstem encephalitis, especially when lesions are definitely found.